MODEL COLLABORATIVE LEARNING INKLUSIF GENDER - Nana Meily Nurdiansyah; Armai Arief; Hudriyah Hudriyah; Robi’atul Hadawiyah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
ABSTRACTIn this paper, we discuss Gender inclusive Collaborative Learning models. Collaborative Learning is working in a team, working together, which is mixed in one group and working together with others for mutual success. The physical activity that stands out in this model is that it can support to be excited in a class that feels hnred so that it can get rid of boredom and move students in learning together. Gender-inclusive learning saves the meaning that in implicating students in analyzing subject matter that has elements or parts that are common, educators divide the group fairly without distinguishing status between students. The purpose of group distribution is fair so that all students get learning. Likewise, Collaborative Learning is used in one learning strategy to improve learning outcomes. The plan focuses on how to foster participation and tenacit y in the learning process and how students can develop their own insights to be able to ha›’e it and there is no difference in learners' gender and social status, all of which are given flexibilit y so that students can learn together. Keywords: Collaborative, Learning, Gender ABSTRAKCollaborative Learning merupakan model pembelajaran yang menekankan kerja sama dalam kelompok belajar dengan tujuan mencapai keberhasilan dalam belajar. Aktivitas fisik yang menonjol dalam model ini adalah mendukung siswa agar bersemangat belajar di dalam kelas sehingga dapat menyingkirkan rasa bosan dan menggerakkan peserta didik dalam belajar secara bersama. Pembelajaran iklusif gender meyimpan arti bahwa dalam mengimplikasikan peserta didik dalam menganalisa materi pelajaran yang mempunyai unsur atau bagian umum, pendidik membagi kelompok dengan adil tanpa membedakan status antar peserta didik. Tujuannya adalah agar mereka mendapat pembelajaran secara merata tanpa harus memandang status laki-perempuan. Begitu pula collaborative learning digunakan pada salah satu strategi pembelajaran untuk meningkatkan hasil belajar yaitu dengan cara peserta didik berkolaborasi individu-kelompok. Rencana tersebut terfokus pada bagaimana menumbuhkan keikutsertaan dan keuletan dalam proses pembelajaran dan agar peserta didik dapat membangun sendiri wawasan mereka sehingga tidak membedakan jenis kelamin dan status sosial, semuanya diberikan keleluasaan agar peseta didik dapat belajar bersama. Kata kunci: Collaborative, Learning, Gender